Growth of the pectoral girdle in a sample of juveniles from the kellis 2 cemetery, Dakhleh Oasis, Egypt. Issue 5 (23rd February 2016) - Bleuze, Michele M.; Wheeler, Sandra M.; Williams, Lana J.; Dupras, Tosha L.
Abstract : Objectives: This study investigates growth patterns in the scapula and clavicle in a cross‐sectional juvenile skeletal sample ranging from 20 weeks gestation to 8.5 years of age from the Kellis 2 cemetery, Dakhleh Oasis, Egypt. The primary goal is to quantify growth patterns and growth velocities in the scapula and clavicle to better understand the development of the pectoral girdle. Methods: A series of low‐order polynomial regression models was used to examine growth curves in clavicle diaphyseal length, scapular height, and scapular width. Incremental growth and relative percent increase were examined among successive age groups as a proxy measure of growth velocity. Scapular body proportions were assessed with the scapular index and compared across age groups using a Kruskal–Wallis test with post‐hoc tests. Results: A third‐order polynomial best describes growth in clavicle diaphyseal length and scapular height, and a second‐order polynomial best describes growth in scapular width. Growth velocity patterns are similar among clavicle diaphyseal length, scapular height, and scapular width particularly from birth until the end of early childhood. Clavicle diaphyseal length decelerates during middle childhood while scapular height and width accelerate during this time. With increasing age, the scapular body proportionately increases more in height than in width. The relatively narrow scapular body characteristic of adult scapulae is first evident during early childhood. Conclusions: Changes in scapular body shape during ontogeny may be a reflection of the greater alterations taking place in the integrated morphology of the pectoral girdle during the biomechanical shift from crawling to bipedalism. Am. J. Hum. Biol. 28:636–645, 2016. © 2016 Wiley Periodicals, Inc.